Base-free oxidation of glucose to gluconic acid using supported gold catalysts. Issue 1 (9th September 2015) - Cao, Yueling; Liu, Xi; Iqbal, Sarwat; Miedziak, Peter J.; Edwards, Jennifer K.; Armstrong, Robert D.; Morgan, David J.; Wang, Junwei; Hutchings, Graham J.
Abstract : 1% Au/TiO2 catalysts prepared by a variety of methods were studied for the base-free oxidation of glucose. Abstract : 1% Au/TiO2 catalysts prepared by a range of preparation methods were studied for the base-free oxidation of glucose. The highest catalytic activity was observed with the catalyst prepared by the sol-immobilization method. Furthermore we have studied the effect of the post-synthesis treatments of treatment with water, or heating in air on the activity. The catalyst calcined at 250 °C showed optimal activity and selectivity. Additionally, we studied the effect of the amount of stabilising ligand in the sol-immobilisation method and observed that this is a key parameter with respect to determining the catalyst's activity.